مهارات ما بعد المعرفة لدى طلاب المدارس الثانوية للمتميزين (Journal Of Educational and Psychological Researches, 2015)
Acquisition of metacognition has an effective and important role in educational process, so it can reduce difficulties faced by learners during theirunderstanding of the subjects.Brown (1980) considers that it is conscious and reflective controlcarried out by the individual in his actions and cognitive responses through the use of self-regulation skills (planning, monitoring and evaluation).The search problem raises through following question: Havestudents  ofhigh school for distinct metacognition?Metacognition is very important  , so the effective learninginvolves planning and goalsetting, and monitoring the progress of the individual and adapted as needed, and allthese activities are metacognition in nature, and through teaching students these skills - which can be taught - we can improve student learning.The importance of current research raises through the following points:1-The concept of metacognitionadds a new dimension and opens the scope andbroad prospects for empirical studies and theoretical discussions on topics of intelligence, memory and thinking and comprehension skills and education.2-Metacognition helps learners to regulateself-behavior and self-awareness through their monitoring of themselves by learning processes .To achieve the objectives of the study, the researchersadopted originalimage of the scale of metacognition which Schraw and Dennison (1994) designed andgot from Kumar study (1998) and the study of Al-Jarrah and Ubaidat (2009) used to measure metacognition at adults and adolescents.The current research has reached the following results:• The research sample individuals possessmetacognition.• There is no statistically significant differencebetween males and females inmetacognition. The researchers found a number of recommendations, andproposals.